Lewis Acid Catalyzed Synthesis of Allocolchicinoids - Mehdi, Mariam A.; Djurdjevic, Sinisa; Green, James R. (Synlett, 2015)
The Lewis acid catalyzed intramolecular conjugate addition of 3′,4′,5′-trimethoxybiphenyl-2-propenones give the corresponding 8,9,10-trimethoxydibenzocycloheptanones in good yields. A case of a conjugate addition–cation rearrangement of a 2′,3′,4′-trimethoxybiphenyl-2-propenone to give the same ring system is also reported. The dibenzocycloheptanones may be converted readily into the 8,9,10-trimethoxy-substituted allocolchicinoids in highly enantioenriched form.
Keywords: Lewis acids; catalysis; Michael addition; cyclization; antitumor agents